Recent Advancements in Serum Albumin-Based Nanovehicles Toward Potential Cancer Diagnosis and Therapy - Shen, Xue; Liu, Xiyang; Li, Tingting; Chen, Yin; Chen, Yang; Wang, Pan; Zheng, Lin; Yang, Hong; Wu, Chunhui; Deng, Shengqi; Liu, Yiyao (Frontiers in Chemistry, 2021)
Recently, drug delivery vehicles based on nanotechnology have significantly attracted the attention of researchers in the field of nanomedicine since they can achieve ideal drug release and biodistribution. Among the various organic or inorganic materials that used to prepare drug delivery vehicles for effective cancer treatment, serum albumin-based nanovehicles have been widely developed and investigated due to their prominent superiorities including good biocompatibility, high stability, non-toxicity, non-immunogenicity, easy preparation and functionalization, allowing them the promising candidates for cancer diagnosis and therapy. This article reviews the recent advances on the applications of serum albumin-based nanovehicles in cancer diagnosis and therapy. We firstly introduce the essential information of bovine serum albumin (BSA) and human serum albumin (HSA), and discuss their drug loading strategies. We then discuss the different types of serum albumin-based nanovehicles including albumin nanoparticles, surface-functionalized albumin nanoparticles, and albumin nanocomplexes. Moreover, after briefly discussing the application of serum albumin-based nanovehicles used as the nanoprobes in cancer diagnosis, we also describe the serum albumin-based nanovehicles-assisted cancer theranostics, involving gas therapy, chemodynamic therapy (CDT), phototherapy (PTT/PDT), sonodynamic therapy (SDT), and other therapies as well as cancer imaging. Numerous studies cited in our review show that serum albumin-based nanovehicles possess the great potential in cancer diagnostic and therapeutic applications.